1983
DOI: 10.1111/j.1432-1033.1983.tb07847.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ribosomal proteins in sea urchin eggs following fertilization

Abstract: Analysis of the ribosomal proteins in sea urchin eggs by two-dimensional polyacrylamide gel electrophoresis revealed postfertilization changes in the proteins of both the small and the large subunits. Five egg-ribosomal proteins (S7, S16, S19, L19, L31) appeared to undergo rapid changes to the corresponding embryo-specific proteins. These changes were completed within 30 min after fertilization, and identical electrophoretic patterns were observed among the different developmental stages of embryos. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This protein was identified for the first time in avian egg white. It has been reported that egg-ribosomal proteins appeared to undergo rapid changes after fertilization, which may be causally related to the acceleration of protein synthesis following fertilization (Takeshima and Nakano, 1983 ). Another Coturnix coturnix specific protein was identified as Lipocalin Q83 (spot A29), which is a lipocalin family member.…”
Section: Resultsmentioning
confidence: 99%
“…This protein was identified for the first time in avian egg white. It has been reported that egg-ribosomal proteins appeared to undergo rapid changes after fertilization, which may be causally related to the acceleration of protein synthesis following fertilization (Takeshima and Nakano, 1983 ). Another Coturnix coturnix specific protein was identified as Lipocalin Q83 (spot A29), which is a lipocalin family member.…”
Section: Resultsmentioning
confidence: 99%
“…The band of the 6-or 6'-subunit after the SDSpolyacrylamide gel electrophoresis for isolation of the subunit was treated with [125I]sodium iodide and then with trypsin by the method of Takeshima & Nakano (17). The labeled digest was first subjected to electrophoresis on a silica gel thinlayer plate (20×20 cm, Silica Gel 60, Merck), then chromatographed on the plate with n-butyl alcohol/ pyridine/acetic acid/water (32.5:25:5:20) as the developing solvent as described previously (17).…”
Section: Tryptic Peptide Mappingmentioning
confidence: 99%
“…The labeled digest was first subjected to electrophoresis on a silica gel thinlayer plate (20×20 cm, Silica Gel 60, Merck), then chromatographed on the plate with n-butyl alcohol/ pyridine/acetic acid/water (32.5:25:5:20) as the developing solvent as described previously (17). The plate was exposed to Fuji RXO-G film with an intensifying screen (Grenex, Fuji) at -7 0°C for 2 days.…”
Section: Tryptic Peptide Mappingmentioning
confidence: 99%
“…(c) The initial activity of monoribosomes from unfertilized eggs is lower, in vitro, than that of ribosomes derived from blástula polyribosomes . Observations on the phosphorylation state of the S6 ribosomal protein, however, cannot yet be correlated with ribosomal activity (Ballinger & Hunt, 1981; Ward et al, 1983;Takeshima & Nakano, 1983;Ballinger et al, 1984).…”
mentioning
confidence: 99%